Question
\( g(n)=n^{2}+4+2 n \) \( h(n)=-3 n+2 \) Find \( (g \cdot h)(1) \)
Ask by Murphy Coleman. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\((g \cdot h)(1) = -7\)
Solution
To find \((g \cdot h)(1)\), we first need to understand that \((g \cdot h)(n)\) represents the product of the functions \(g(n)\) and \(h(n)\). Therefore:
\[
(g \cdot h)(n) = g(n) \times h(n)
\]
Given the functions:
\[
g(n) = n^2 + 2n + 4
\]
\[
h(n) = -3n + 2
\]
Let's evaluate each function at \(n = 1\):
1. **Calculate \(g(1)\):**
\[
g(1) = (1)^2 + 2(1) + 4 = 1 + 2 + 4 = 7
\]
2. **Calculate \(h(1)\):**
\[
h(1) = -3(1) + 2 = -3 + 2 = -1
\]
3. **Multiply the results:**
\[
(g \cdot h)(1) = g(1) \times h(1) = 7 \times (-1) = -7
\]
**Final Answer:** \(-7\)
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Beyond the Answer
To find \( (g \cdot h)(1) \), we first need to calculate \( g(1) \) and \( h(1) \). Starting with \( g(n) = n^2 + 2n + 4 \): \[ g(1) = 1^2 + 2(1) + 4 = 1 + 2 + 4 = 7 \] Next, for \( h(n) = -3n + 2 \): \[ h(1) = -3(1) + 2 = -3 + 2 = -1 \] Now we find \( (g \cdot h)(1) \): \[ (g \cdot h)(1) = g(1) \cdot h(1) = 7 \cdot (-1) = -7 \] Thus, \( (g \cdot h)(1) = -7 \).